The Relationship among Dyadic Adjustment and Disease Burden in Patients with Bipolar Disorder and Their Spouses - Zeynep Namlı; Lut Tamam; Mehmet Emin Demirkol; Mahmut Onur Karaytuğ; Caner Yeşiloğlu; Kerim Uğur (Behavioral Sciences, 2023)
(1) Background: Spouses of individuals with bipolar disorder (BD) experience significant burdens, and the perception of the burden may affect dyadic adjustment. We aimed to investigate the sexual functions, alexithymic traits, marital satisfaction, and burden in patients with BD and their spouses. We also aimed to assess the mediating role of sexual functions and alexithymia in the relationship between burden and dyadic adjustment. (2) Methods: We included 81 patients with BD type 1 (40.69 ± 8.55 years, 65.4% female, and 34.6% male) and their healthy spouses (40.95 ± 7.30 years, 34.6% female, and 65.4% male) and 78 healthy controls (38.90 ± 5.88, 48.7% female, and 51.3% male). The participants were evaluated using the Golombok–Rust Inventory of Sexual Satisfaction (GRISS), Dyadic Adjustment Scale (DAS), Hamilton Depression Rating Scale (HDRS), Toronto Alexithymia Scale-20 (TAS-20), and Burden Assessment Scale (BAS). (3) Results: The GRISS scores of the control group were significantly lower than the spouses and BD groups. The DAS total score of the control group was significantly higher than that of the spouses and BD groups. Regression analyses revealed that TAS, GRISS, and HDRS scores were associated with DAS scores in the BD group. In the spouse group, TAS and BAS scores were associated with DAS scores. The GRISS scores partially mediated the relationship between dyadic adjustment and burden in the spouses of patients with BD. (4) Conclusions: Mental health professionals should regularly scan caregivers’ perceptions of burden. Appropriate psychosocial interventions could help spouses of patients with BD to cope better with the burden and improve dyadic adjustment.